Method for high-pressure shearing of synthetic material
By adding hard particles to high-pressure synthesis to reduce the synthesis pressure, the problem of low product generation efficiency due to small sample cavity volume in existing high-pressure synthesis equipment is solved, efficient new material synthesis is achieved, and the industrialization of materials is promoted.
Patent Information
- Application Number
- CN202411798406.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-28
AI Technical Summary
In the existing high-pressure synthesis methods, the small sample cavity volume of the equipment leads to low product generation efficiency, which limits the industrialization of new materials.
During the high-pressure synthesis process, hard particles are added to reduce the synthesis pressure and improve the synthesis efficiency. The hardness of the hard particles is greater than that of the raw materials and does not react chemically with the raw materials. It can generate shear force on the raw materials under high pressure conditions and reduce the pressure required for the reaction.
By adding hard particles, the high-pressure synthesis pressure of the material is significantly reduced, the efficiency of synthesising new materials under high pressure is improved, and the sample cavity volume of the synthesis equipment can be expanded without adding new equipment, and the product generation efficiency can be improved.
Smart Images

Figure CN119701776A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a material synthesis method, and more particularly to a high-pressure shearing method for synthesizing materials. Background Art
[0002] High pressure synthesis refers to the process of synthesizing materials with specific structures and properties by physical or chemical methods under high pressure (often high temperature) conditions. This method is usually used to prepare materials that are difficult to synthesize under conventional conditions, or to improve the performance of materials. It is an important material preparation technology. From the perspective of the state change of the products of high pressure synthesis, there are two types of synthetic products: one is that after a certain substance is subjected to high pressure, the composition of the product remains unchanged, but a polymorphic phase change of the crystal structure occurs, forming a new substance; the other is that after a certain material system is subjected to high pressure, chemical combinations between elements or different substances occur, forming new compounds and new substances.
[0003] Materials synthesized under high pressure usually have unique physical, chemical and mechanical properties, which make them play an important role in many high-tech fields and industrial applications. For example, room temperature superconducting materials have important applications in maglev trains, magnetic resonance imaging (MRI), particle accelerators and other fields. Diamond, due to its extremely high hardness and wear resistance, is widely used in cutting tools, abrasives, drill bits, decorations (diamonds), etc. New alloys such as superalloys are used to manufacture aircraft engine parts, gas turbines, chemical equipment, etc., and have excellent performance in high temperature, high pressure and corrosive environments. New ceramic materials: silicon nitride (Si3N4), silicon carbide (SiC). These materials have high hardness, high wear resistance and high temperature resistance, and are used for cutting tools, high temperature structural components, bulletproof armor, etc. These are all materials synthesized under high pressure, which are not common in nature or cannot be directly obtained.
[0004] The high pressure required for high-pressure synthesis usually refers to more than 1GPa. At present, the equipment (synthesis equipment) that can provide a high-pressure environment for synthesizing new materials is usually a polyhedron press, a diamond anvil press, etc. Among them, ① two-sided top press: pressure 20-25GPa, maximum temperature can reach 2500℃, maximum cavity 1.8mm (diameter); ② six-sided top press: pressure below 7.5GPa, temperature below 2000℃, maximum cavity 28mm (diameter); ③ top anvil press: can achieve pressures of tens to hundreds of GPa, laser heating can reach a high temperature of 4000℃, and the sample cavity is 5-150μm. Generally, the higher the synthesis pressure, the smaller the sample cavity of the corresponding equipment used.
[0005] For the above-mentioned synthesis equipment, it is usually impossible to expand the volume of the sample chamber of the synthesis equipment while ensuring that the pressure provided can meet the synthesis pressure. When the number of equipment remains unchanged, the size of the sample chamber volume determines the production efficiency of the product; the larger the volume of the sample chamber, the higher the production efficiency of the product; the smaller the volume of the sample chamber, the lower the production efficiency of the product. Since the volume of the sample chamber of the existing synthesis equipment is usually small, the production efficiency of the product is low, which makes it impossible to industrialize the new material. Summary of the invention
[0006] In view of the technical problem of low product generation efficiency in existing high-pressure synthesis methods, the present invention provides a method for synthesizing materials by high-pressure shearing.
[0007] The invention reduces the synthesis pressure and improves the synthesis efficiency by adding hard particles into the raw materials during the high-pressure synthesis process.
[0008] The object of the present invention is to provide a method for high-pressure shearing of synthetic materials.
[0009] The method comprises adding hard particles into a raw material; the hardness of the hard particles is greater than the hardness of the raw material; and the hard particles do not chemically react with the raw material.
[0010] Shear force refers to the force that acts along a certain plane inside an object and causes the object to slide relative to itself. More specifically, when an external force acts on an object, if the direction of this force is parallel to a certain plane on the surface of the object and the magnitude of the force is sufficient to overcome the friction inside the object, then the object will move relative to this plane. This force is called shear force.
[0011] Hard particles are added to the raw materials, the hardness of the hard particles is greater than the hardness of the raw materials, and the hard particles do not chemically react with the raw materials; under the high pressure conditions and in the process of applying pressure to the raw materials, the hard particles in the raw materials will generate a shear force on the raw materials under the action of pressure, and the shear force is perpendicular to the direction of pressure, which can reduce the reaction formation energy of the raw materials, thereby reducing the pressure required for the raw material reaction, resulting in the effect of reducing the synthesis pressure.
[0012] The method uses a device capable of providing a high-pressure environment; the device capable of providing a high-pressure environment comprises a sample chamber; the raw material and hard particles are placed in the sample chamber. The device capable of providing a high-pressure environment provides pressure for the raw material in the sample chamber.
[0013] The equipment capable of providing a high-pressure environment may be selected from a six-sided top press, a two-sided top press or a diamond anvil press.
[0014] Generally, the size of the pressure that the device capable of providing a high-pressure environment can provide is inversely proportional to the size of its sample chamber, that is, the higher the pressure that can be provided, the smaller the sample chamber. The method of the present invention can effectively reduce the required synthesis pressure, so the pressure required to be provided by the device capable of providing a high-pressure environment (synthetic device) is reduced. Therefore, the sample chamber volume of the synthetic device can be expanded within the range of pressure reduction. When the number of synthetic devices remains unchanged, the sample chamber volume is expanded, so that the amount of a single synthetic product is increased, thereby improving the synthesis efficiency of the product.
[0015] The hard particles may be any one or more material particles whose mass and chemical properties do not change before and after high pressure synthesis and whose hardness is greater than that of the raw material; for example, they may be selected from diamond particles, which have the highest hardness in nature. They may also be selected from one or more of cubic boron nitride, amorphous boron, silicon dioxide, tungsten carbide, corundum particles, and other hard particles.
[0016] Any hard particle size can provide shear force and reduce the required synthesis pressure. However, hard particles of appropriate particle size can make the raw material shear more uniform and reduce the required synthesis pressure; therefore, as a preferred embodiment, the hard particles have a particle size of 0.1 to 100 μm.
[0017] Any amount of hard particles can provide shear force and reduce the required synthesis pressure. The more hard particles are used, the more uniform the raw material shearing can be and the lower the required synthesis pressure; however, the sample chamber capacity is fixed, and the more hard particles are used, the less raw material is added, which leads to a decrease in the amount of single product and a decrease in product synthesis efficiency. Therefore, considering the required synthesis pressure and product synthesis efficiency, as a preferred solution, the volume of hard particles relative to the raw material is 20-50%.
[0018] The method of the present invention can be used for the synthesis of any material that can be synthesized by the existing high-pressure synthesis method; for example, it can be used for the synthesis of graphite, diamond, etc.
[0019] When used for the synthesis of graphite, a high-pressure shear synthesis method of graphite includes: using carbonate, such as MgCO3, as a raw material, adding diamond, cubic boron nitride, amorphous boron, silicon dioxide, tungsten carbide, and corundum as hard particles to the raw material; after mixing the raw material and the hard particles, placing them in a sample chamber of a device that can provide a high-pressure environment, and reacting under high-pressure conditions; the high pressure is greater than or equal to 0.1GPa, preferably 0.5-30GPa; the reaction temperature is greater than or equal to 300°C, preferably 300-2000°C.
[0020] The particle size of the cubic boron nitride or tungsten carbide is 0.1-100 μm.
[0021] The volume ratio of the cubic boron nitride or tungsten carbide to the MgCO3 is (20-50):100.
[0022] The equipment capable of providing a high-pressure environment is a high-pressure device, preferably a six-sided large-cavity press or a diamond anvil press.
[0023] At present, under high pressure conditions, graphite cannot be synthesized directly from carbonate without adding hard particles. The present invention successfully synthesizes graphite from carbonate as raw material by adding hard particles, and the minimum pressure required is only 0.1GPa.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The method of the present invention can significantly reduce the high-pressure synthesis pressure of the material and can effectively improve the efficiency of synthesizing new materials under high pressure without adding new equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a microscopic photograph of the product prepared in Example 1 of the present invention;
[0027] Figure 2 This is a Raman spectrum of the product prepared in Example 1 of the present invention;
[0028] Figure 3 The Raman spectra of the products prepared in Examples 2-5 of the present invention are shown in FIG. 1 , wherein Curve I is the Raman spectrum of the product of Example 2, Curve II is the Raman spectrum of the product of Example 5, Curve III is the Raman spectrum of the product of Example 3, and Curve IV is the Raman spectrum of the product of Example 4;
[0029] Figure 4 This is a Raman spectrum of the product prepared in Example 6 of the present invention;
[0030] Figure 5 This is a Raman spectrum of the product prepared in Example 9 of the present invention;
[0031] Figure 6 This is a Raman spectrum of the product prepared in Example 10 of the present invention;
[0032] Figure 7 The Raman spectra of magnesium carbonate before and after the pressurized reaction in Comparative Example 1 are shown;
[0033] Figure 8 The Raman spectra of magnesium carbonate before and after the pressurized reaction in Comparative Example 2 are shown;
[0034] Figure 2-7 In the figure, the horizontal axis is the wave number and the vertical axis is the signal intensity. DETAILED DESCRIPTION
[0035] The present invention is described in detail below in conjunction with specific drawings and embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the content of the present invention still fall within the scope of protection of the present invention.
[0036] The raw materials used in the following examples and comparative examples are all commercially available products; the source is Aladdin.
[0037] Example 1
[0038] Synthesis of graphite:
[0039] The raw material is magnesium carbonate with a purity of 99.99%, the hard particles are cubic boron nitride, the particle size of the cubic boron nitride is 100nm, and the equipment is a diamond anvil press.
[0040] Operation: Mix cubic boron nitride and magnesium carbonate evenly in a volume ratio of 1:1, then fill them into the sample chamber of the diamond anvil press, pressurize to 0.5 GPa, temperature to 300°C, keep warm for 10 minutes, and take out the product.
[0041] Product form Figure 1 The product was tested by Raman spectroscopy, and the following Figure 2 Raman spectrum shown. Figure 2 In the figure, Raman spectrum I is the Raman spectrum of the raw material MgCO3, Raman spectrum II is the Raman spectrum of cubic boron nitride, Raman spectrum III is the Raman spectrum of hexagonal boron nitride, and Raman spectrum IV is the Raman spectrum of graphite. It shows that the product contains graphite, and graphite is synthesized in this embodiment.
[0042] Example 2
[0043] Synthesis of graphite
[0044] The raw material is magnesium carbonate with a purity of 99.99%, the hard particles are cubic boron nitride, the particle size of the cubic boron nitride is 100nm, and the equipment is a diamond anvil press.
[0045] Operation: Mix cubic boron nitride and magnesium carbonate evenly in a volume ratio of 1:1, then fill them into the sample chamber of the diamond anvil press, pressurize to 5 GPa, keep the temperature at 23°C, maintain for 10 minutes, and take out the product.
[0046] The product was tested by Raman spectroscopy and the following results were obtained: Figure 3 The Raman spectrum shown in the middle curve I shows that graphite is synthesized in this embodiment.
[0047] Example 3
[0048] Synthesis of graphite
[0049] The raw material is magnesium carbonate with a purity of 99.99%, the hard particles are cubic boron nitride, the particle size of the cubic boron nitride is 100nm, and the equipment is a diamond anvil press.
[0050] Operation: Mix cubic boron nitride and magnesium carbonate evenly in a volume ratio of 1:1, then fill them into the sample chamber of the diamond anvil press, pressurize to 10 GPa, temperature to 23°C, maintain for 10 minutes, and take out the product.
[0051] The product was tested by Raman spectroscopy and the following results were obtained: Figure 3 The Raman spectrum shown in curve III in the middle shows that graphite is synthesized in this embodiment.
[0052] Example 4
[0053] Synthesis of graphite
[0054] The raw material is magnesium carbonate with a purity of 99.99%, the hard particles are cubic boron nitride, the particle size of the cubic boron nitride is 100nm, and the equipment is a diamond anvil press.
[0055] Operation: Mix cubic boron nitride and magnesium carbonate evenly in a volume ratio of 1:1, then fill them into the sample chamber of the diamond anvil press, pressurize to 20 GPa, temperature to 23°C, react for 10 minutes, and take out the product.
[0056] The product was tested by Raman spectroscopy and the following results were obtained: Figure 3 The Raman spectrum shown in curve IV in the middle shows that graphite is synthesized in this embodiment.
[0057] Example 5
[0058] Synthesis of graphite
[0059] The raw material is magnesium carbonate with a purity of 99.99%, the hard particles are cubic boron nitride, the particle size of the cubic boron nitride is 100nm, and the equipment is a diamond anvil press.
[0060] Operation: Mix cubic boron nitride and magnesium carbonate evenly in a volume ratio of 1:1, then fill them into the sample chamber of the diamond anvil press, pressurize to 30 GPa, temperature to 23°C, react for 10 minutes, and take out the product.
[0061] The product was tested by Raman spectroscopy and the following results were obtained: Figure 3 The Raman spectrum shown in curve II in the middle shows that graphite is synthesized in this embodiment.
[0062] Example 6
[0063] Synthesis of graphite
[0064] The raw material is magnesium carbonate with a purity of 99.99%, and the hard particles are tungsten carbide with a particle size of 100nm. The equipment is a diamond anvil press.
[0065] Operation: Evenly mix tungsten carbide and magnesium carbonate in a volume ratio of 1:1, then fill them into the sample chamber of the diamond anvil press, pressurize to 0.5 GPa, temperature to 300°C, react for 10 minutes, and take out the product.
[0066] The product was tested by Raman spectroscopy and the following results were obtained: Figure 4 Raman spectrum shown. Figure 4 It is explained that graphite was synthesized in this embodiment.
[0067] Example 7
[0068] Synthesis of graphite
[0069] The raw material is magnesium carbonate with a purity of 99.99%, the hard particles are silicon dioxide, and the particle size of silicon dioxide is 1 μm. The equipment is a diamond anvil press.
[0070] Operation: Mix silicon dioxide and magnesium carbonate evenly in a volume ratio of 1:1, then fill them into the sample chamber of the diamond anvil press, pressurize to 0.5 GPa, temperature to 300°C, react for 10 minutes, and take out the product.
[0071] The product was subjected to Raman spectroscopy test, and according to the test results, it was concluded that graphite was synthesized in this embodiment.
[0072] Example 8
[0073] Synthesis of graphite
[0074] The raw material is magnesium carbonate with a purity of 99.99%, the hard particles are cubic boron nitride, and the particle size of the cubic boron nitride is 100 μm. The equipment uses a diamond anvil press.
[0075] Operation: Mix cubic boron nitride and magnesium carbonate evenly in a volume ratio of 3:1, then fill them into the sample chamber of the diamond anvil press, pressurize to 0.5 GPa, temperature to 300°C, react for 10 minutes, and take out the product.
[0076] The product was subjected to Raman spectroscopy test, and according to the test results, it was concluded that graphite was synthesized in this embodiment.
[0077] Example 9
[0078] Synthesis of graphite
[0079] The raw material is magnesium carbonate with a purity of 99.99%, and the hard particles are corundum with a particle size of 100 μm. The equipment is a diamond anvil press.
[0080] Operation: Evenly mix corundum and magnesium carbonate in a volume ratio of 3:1, then fill them into the sample chamber of the diamond anvil press, pressurize to 0.5 GPa, temperature to 300°C, react for 10 minutes, and take out the product.
[0081] The product was tested by Raman spectroscopy and the following results were obtained: Figure 5 Raman spectrum shown. Figure 5 In the figure, the black curve is the Raman spectrum of the raw material MgCO3, the green curve is the Raman spectrum of corundum, and the blue curve is the Raman spectrum of graphite. Figure 5 It is explained that graphite was synthesized in this embodiment.
[0082] Example 10
[0083] Diamond Synthesis
[0084] The raw material is magnesium carbonate with a purity of 99.99%, and the hard particles are amorphous boron with a particle size of 1 μm. The equipment is a diamond anvil press.
[0085] Operation: Mix cubic boron nitride and magnesium carbonate evenly in a volume ratio of 1:1, then fill them into the sample chamber of the diamond anvil press, pressurize to 22.5 GPa, temperature to 1500°C, react for 10 minutes, and take out the product.
[0086] The product was tested by Raman spectroscopy and the following results were obtained: Figure 6 Raman spectrum shown. Figure 6 It is explained that diamond was synthesized in this embodiment.
[0087] Comparative Example 1
[0088] Magnesium carbonate with a purity of 99.99% was loaded into a diamond anvil press, pressurized to 40 GPa, and the temperature was 300° C. After reacting for 1 day, the product was taken out.
[0089] The product was tested by Raman spectroscopy and the following results were obtained: Figure 7 Raman spectrum shown. Figure 7 In the figure, the black curve is the Raman spectrum of magnesium carbonate, and the red curve is the Raman spectrum of magnesium carbonate after pressure reaction. Figure 7 It shows that magnesium carbonate remains magnesium carbonate after the pressurized reaction, and no characteristic peak of graphite appears, so no graphite is synthesized.
[0090] Comparative Example 2
[0091] Magnesium carbonate with a purity of 99.99% was loaded into a diamond anvil press, pressurized to 22.5 GPa, heated to 1500° C. by laser, reacted for 1 hour, and the product was taken out.
[0092] The product was tested by Raman spectroscopy and the following results were obtained: Figure 8 Raman spectrum shown. Figure 8 In the figure, the black curve is the Raman spectrum of magnesium carbonate, and the red curve is the Raman spectrum of magnesium carbonate after pressure reaction. Figure 8 It shows that magnesium carbonate remains magnesium carbonate after the pressurized reaction, and no characteristic peak of graphite appears, so no graphite is produced.
Claims
1. A method for high pressure shearing of synthetic materials, characterized in that: The method comprises adding hard particles into a raw material; the hardness of the hard particles is greater than the hardness of the raw material; and the hard particles do not chemically react with the raw material.
2. The method according to claim 1, characterized in that The hard particles are selected from at least one of diamond, cubic boron nitride, amorphous boron, silicon dioxide, tungsten carbide and corundum particles.
3. The method according to claim 1, characterized in that The particle size of the hard particles is 0.1 to 100 μm.
4. The method according to claim 1, characterized in that The volume amount of the hard particles relative to the raw material is 20-50%.
5. The method according to claim 1, characterized in that The materials are graphite and diamond.
6. The method according to claim 1, characterized in that High pressure synthesis is performed using equipment that can provide a high pressure environment.
7. The method according to claim 6, characterized in that The equipment capable of providing a high-pressure environment is selected from a six-sided top press, a two-sided top press or a diamond anvil press.
8. The method according to claim 6, characterized in that The device capable of providing a high-pressure environment comprises a sample chamber; the raw material and hard particles are placed in the sample chamber.
9. A high-pressure shear synthesis method for graphite, characterized in that: The method comprises the following steps: using carbonate as a raw material, adding diamond, cubic boron nitride, amorphous boron, silicon dioxide, tungsten carbide and corundum as hard particles to the raw material; mixing the raw material and the hard particles and placing them in a sample chamber of a device capable of providing a high-pressure environment, and reacting under high-pressure conditions; the high pressure is greater than or equal to 0.1 GPa, preferably 0.5 to 30 GPa; and the reaction temperature is greater than or equal to 300° C., preferably 300 to 2000° C.
10. The method according to claim 9, characterized in that The particle size of the cubic boron nitride or tungsten carbide is 0.1 to 100 μm; or / and, The volume ratio of the cubic boron nitride or tungsten carbide to the MgCO3 is (20-50):100; or / and, The equipment capable of providing a high-pressure environment is a high-pressure device, preferably a six-sided large-cavity press or a diamond anvil press.